Flow-Directed Catheters in Hepatic Embolization Therapy—A Review with Clinical Cases - Iqbal, Shams; Breyfogle, Lawrence Jordan; Flacke, Sebastian (Journal of Clinical Interventional Radiology ISVIR, 2021)
Transarterial embolization with chemotherapy and radiation is well-documented forms of treatment for liver cancers but reflux of embolic particles to nontarget tissues can result in unintended consequences such as gastrointestinal ulceration. Traditionally, operators have used coil embolization of hepatoenteric collaterals to prevent reflux. Antireflux microcatheters that contain expandable baskets (Surefire) or inflatable balloons have recently been developed as tools to avoid these side effects. We describe cases where antireflux catheters were used instead of coil embolization. Using antireflux catheters, we eliminated particle reflux into nontarget vessels. We also review the literature on antireflux catheters involved in preventing reflux during chemo- and radioembolization.
Keywords: hepatic embolization; flow-directed catheters; antireflux catheters